White Lies - Erat, Sanjiv; Gneezy, Uri (Management science, 2012)
In this paper we distinguish between two types of white lies: those that help others at the expense of the person telling the lie, which we term altruistic white lie s, and those that help both others and the liar, which we term Pareto white lies . We find that a large fraction of participants are reluctant to tell even a Pareto white lie, demonstrating a pure lie aversion independent of any social preferences for outcomes. In contrast, a nonnegligible fraction of participants are willing to tell an altruistic white lie that hurts them a bit but significantly helps others. Comparing white lies to those where lying increases the liar's payoff at the expense of another reveals important insights into the interaction of incentives, lying aversion, and preferences for payoff distributions. Finally, in line with previous findings, women are less likely to lie when it is costly to the other side. Interestingly though, we find that women are more likely to tell an altruistic lie. This paper was accepted by Teck Ho, decision analysis.